Factors associated with community acquired severe pneumonia among under five children in Dhaka, Bangladesh: A case control analysis - Sabiha Nasrin; Md. Tariqujjaman; Marufa Sultana; Rifat A. Zaman; Shahjahan Ali; Mohammod J. Chisti; Abu S. G. Faruque; Tahmeed Ahmed; George J. Fuchs; Niklaus Gyr; Nur H. Alam (PLoS ONE, 2022)
Background Pneumonia is the leading cause of death in children globally with the majority of these deaths observed in resource-limited settings. Globally, the annual incidence of clinical pneumonia in under-five children is approximately 152 million, mostly in the low- and middle-income countries. Of these, 8.7% progressed to severe pneumonia requiring hospitalization. However, data to predict children at the greatest risk to develop severe pneumonia from pneumonia are limited. Method Secondary data analysis was performed after extracting relevant data from a prospective cluster randomized controlled clinical trial; children of either sex, aged two months to five years with pneumonia or severe pneumonia acquired in the community were enrolled over a period of three years in 16 clusters in urban Dhaka city. Results The analysis comprised of 2,597 children aged 2–59 months. Of these, 904 and 1693 were categorized as pneumonia (controls) and severe pneumonia (cases), respectively based on WHO criteria. The median age of children was 9.2 months (inter quartile range, 5.1–17.1) and 1,576 (60%) were male. After adjustment for covariates, children with temperature ≥38°C, duration of illness ≥3 days, male sex, received prior medical care and severe stunting showed a significantly increased likelihood of developing severe pneumonia compared to those with pneumonia. Severe pneumonia in children occurred more often in older children who presented commonly from wealthy quintile families, and who often sought care from private facilities in urban settings. Conclusion and recommendation Male sex, longer duration of illness, fever, received prior medical care, and severe stunting were significantly associated with development of WHO-defined severe childhood pneumonia in our population. The results of this study may help to develop interventions target to reduce childhood morbidity and mortality of children suffering from severe pneumonia.